Carbon-coated lithium-containing phosphate positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery
By using presintered carbon to coat the lithium phosphate positive electrode material, the problems of insufficient conductivity and cyclic performance are solved, and better electrochemical performance and cyclic performance are achieved.
Patent Information
- Application Number
- CN202411978168.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
The ion conductivity and electron conductivity of the lithium-containing phosphate positive electrode material are low, which limits the charge and discharge rate and overall performance of lithium-ion batteries. The nano-scaling and carbon coating methods are prone to trigger side reactions and affects the battery circulation performance.
Presintered carbon is used as the carbon source of the carbon cladding layer, and a carbon cladding with better conductivity is obtained through high-temperature sintering treatment. By controlling the particle size and specific surface area, surface functional groups are reduced and side reactions are reduced.
The conductivity and cyclic stability of the carbon-coated lithium phosphate-containing positive electrode material is improved, and the electrochemical performance and cyclic performance of lithium-ion batteries are improved.
Smart Images

Figure CN119725488A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon-coated lithium phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace devices and other fields due to their high energy density, long life and environmental protection. With the rapid development of electric vehicles and energy storage markets, higher requirements are placed on the performance of lithium-ion batteries. The positive electrode material of lithium-ion batteries is one of the key factors that determine battery performance. Compared with traditional positive electrode materials, such as lithium cobalt oxide (LiCoO 2) and nickel-cobalt-manganese ternary materials (NCM), containing lithium phosphates such as lithium manganese phosphate, lithium vanadium phosphate, lithium iron phosphate and lithium manganese iron phosphate, have attracted much attention due to their low cost and high safety.
[0003] Lithium-ion batteries prepared using lithium-containing phosphates have the advantages of high safety, long life, good low-temperature performance, and low cost. However, lithium-containing phosphates also have some inherent defects. In the crystal structure of lithium-containing phosphates, the diffusion path of lithium ions is relatively complex, resulting in low ion conductivity; at the same time, its electronic conductivity is also poor, which limits the charge and discharge rate and overall performance of the battery. In order to overcome these defects, researchers usually use particle nano-sizing and surface carbon coating methods. However, both particle nano-sizing and surface carbon coating are prone to induce side reactions during the battery cycle, generating by-products that increase the internal resistance of the battery and affect the battery's cycle performance. Therefore, how to improve the battery's cycle performance and electrochemical performance while improving the conductivity and ion conductivity of lithium manganese iron phosphate has become an important issue that needs to be urgently addressed in the field of lithium-ion batteries. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a carbon-coated lithium phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a lithium ion battery. The carbon-coated lithium phosphate positive electrode material has the advantages of good conductivity, few surface functional groups and small specific surface area, which is beneficial to the capacity of the lithium ion battery and can improve the electrochemical performance and cycle performance of the lithium ion battery.
[0005] The specific technical solutions of the present invention are as follows: In a first aspect, the present invention provides a carbon-coated lithium-phosphate positive electrode material, wherein the particles of the lithium-phosphate positive electrode material have a composite structure, wherein the composite structure comprises a lithium-phosphate core and a carbon coating layer at least partially coated on the outside of the lithium-phosphate core, wherein the carbon source of the carbon coating layer is pre-sintered carbon, and the carbon coating layer is g / I d ≥1.
[0006] Furthermore, the proportion of functional groups on the surface of the carbon-coated lithium phosphate positive electrode material is less than 1%.
[0007] Furthermore, the particle size of the particles is 0.1-20 μm and the SPAN value is 9-10.
[0008] Furthermore, the powder impedance of the carbon-coated lithium phosphate positive electrode material is less than 1000 Ω.
[0009] Furthermore, the thickness of the carbon coating layer is 0.5-20 nm.
[0010] Furthermore, the lithium-containing phosphate includes at least one of lithium manganese phosphate, lithium iron phosphate and lithium manganese iron phosphate.
[0011] Furthermore, when the lithium-containing phosphate is lithium manganese iron phosphate, the median particle size D of the particles is 50 1-1.2μm.
[0012] Furthermore, when the lithium-containing phosphate is lithium iron phosphate, the median particle size D of the particles is 50 1.8-2 μm.
[0013] In a second aspect, the present invention also provides a method for preparing the above-mentioned carbon-coated lithium phosphate positive electrode material, comprising the following steps: S1. The organic carbon material and / or the inorganic carbon material is subjected to sintering treatment to obtain pre-sintered carbon; the sintering treatment temperature is 800-1200°C and the time is more than 3 hours; S2, chemically reacting raw materials including a phosphorus source, a lithium source, an iron source and / or a manganese source and sintering the raw materials to obtain a lithium-containing phosphate; S3. The lithium-containing phosphate described in step S2 and the pre-sintered carbon described in step S1 are mixed, sintered and crushed to obtain a carbon-coated lithium-containing phosphate positive electrode material.
[0014] Furthermore, the inorganic carbon material in step S1 includes at least one of graphite, carbon nanotubes, graphene, acetylene black, carbon fiber, carbon black, hard carbon, soft carbon and graphyne.
[0015] Furthermore, the organic carbon material in step S1 includes at least one of glucose, fructose, sucrose, maltose, starch, cellulose, citric acid, polyols, ascorbic acid, polyaniline, polyvinylidene fluoride, polytetrafluoroethylene, acrylonitrile and cyanamide and their derivatives.
[0016] Furthermore, the sintering treatment in step S1 is performed at a temperature of 1000-1200° C. and for a time of 5-10 h.
[0017] Furthermore, the chemical reaction in step S2 adopts at least one of a sol-gel method, a solid phase reaction method, a hydrothermal method, a spray drying method and a co-precipitation method.
[0018] Furthermore, the iron source in step S2 includes at least one of iron-containing phosphates, hydrogen phosphates, dihydrogen phosphates, carbonates, formates, acetates, oxides, citrates, oxalates and chlorides.
[0019] Furthermore, the lithium source in step S2 includes at least one of lithium-containing phosphates, hydrogen phosphates, dihydrogen phosphates, carbonates, formates, acetates, oxides, citrates, oxalates and chlorides.
[0020] Furthermore, the manganese source in step S2 includes at least one of manganese-containing phosphates, hydrogen phosphates, dihydrogen phosphates, carbonates, formates, acetates, oxides, citrates, oxalates and chlorides.
[0021] Furthermore, the phosphorus source in step S2 includes at least one of phosphate, dihydrogen phosphate and phosphoric acid.
[0022] Furthermore, the sintering temperature in step S2 and step S3 is 500-800° C. and the sintering time is 4-12 h.
[0023] Furthermore, the molar ratio of the manganese source, the iron source, the phosphorus source and the lithium source in the raw material of step S2 is (1-x):x:1:1.01, wherein 0≤x≤1.
[0024] Furthermore, in step S3, the mass ratio of the phosphate content to the pre-sintered carbon is 1:(0.005-0.03).
[0025] In a third aspect, the present invention further provides a positive electrode plate, which is prepared from the above-mentioned carbon-coated lithium phosphate positive electrode material.
[0026] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery adopts the above-mentioned positive electrode plate.
[0027] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.
[0028] The reagents and raw materials used in the present invention are commercially available.
[0029] The positive and progressive effects of the present invention are: The carbon-coated lithium phosphate positive electrode material provided by the present invention adopts pre-sintered carbon sintered at high temperature in advance as the carbon source of the carbon coating layer. The pre-sintered carbon has stronger conductivity and fewer surface functional groups. It is introduced into the synthesis process of the lithium phosphate positive electrode material as a carbon coating layer to obtain a carbon-coated lithium phosphate positive electrode material with relatively large particles, relatively small specific surface area, fewer surface functional groups and better conductivity. The carbon-coated carbon coating layer of the carbon-coated lithium phosphate positive electrode material has a high graphitization ratio and better conductivity; the carbon-coated manganese phosphate material has large particles and a small specific surface area, which can reduce the contact area with the battery electrolyte and reduce the occurrence of side reactions; the pre-sintered carbon has been transformed into a carbon material with a low content of surface functional groups during the high-temperature pre-sintering process. Compared with the carbon material with a high content of surface functional groups, the carbon coating layer formed by the pre-sintered carbon can reduce the catalytic decomposition of the electrolyte. The carbon-coated lithium phosphate positive electrode material is conducive to the capacity of lithium-ion batteries, and can improve the cycle performance of lithium-ion batteries and enhance the electrochemical performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 1 is a data graph of the capacity retention rate of the samples prepared in Example 1 and Comparative Example 1.
[0031] Figure 2 Schematic diagram of the DC resistance change rate of the samples prepared in Example 1 and Comparative Example 1.
[0032] Figure 3 It is the infrared absorption spectra of the samples prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0034] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0035] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0036] As described in the background technology, although nano-sizing can significantly increase the specific surface area of lithium-containing phosphate materials, thereby improving their electrochemical activity, carbon coating can improve the conductivity of materials and reduce charge transfer resistance. However, nano-sizing increases the specific surface area of materials, but also increases the surface area to volume ratio of materials, resulting in more surface defects and inhomogeneities. These defects and inhomogeneities may cause side reactions during the battery cycle and generate by-products, thereby increasing the internal resistance of the battery and affecting its cycle performance. Although carbon coating improves the conductivity of the material, due to the large number of functional groups remaining on the surface of the material, these functional groups may react with the electrolyte during the battery cycle to generate irreversible by-products, further increasing the internal resistance of the battery and affecting its cycle performance.
[0037] In order to solve the above technical problems, the embodiments of the present invention provide a carbon-coated lithium-phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a lithium-ion battery. The carbon-coated lithium-phosphate positive electrode material uses pre-sintered carbon sintered at high temperature in advance as the carbon source of the carbon coating layer. The pre-sintered carbon has stronger conductivity and fewer surface functional groups. It is introduced into the synthesis process of the lithium-phosphate positive electrode material as a carbon coating layer to obtain a carbon-coated lithium-phosphate positive electrode material with relatively large particles, relatively small specific surface area, fewer surface functional groups and better conductivity. The positive electrode plate and lithium battery prepared using the lithium-phosphate positive electrode material have good electrochemical performance and cycle performance.
[0038] In a first aspect, the present invention provides a carbon-coated lithium phosphate positive electrode material, wherein the particles of the lithium phosphate positive electrode material have a composite structure, the composite structure comprises a lithium phosphate core and a carbon coating layer at least partially coated on the outside of the lithium phosphate core, wherein the carbon source of the carbon coating layer is pre-sintered carbon, and the carbon coating layer has a carbon content of about 100%. g / I d ≥1.
[0039] The carbon-coated lithium-containing phosphate positive electrode material provided by the present invention adopts pre-sintered carbon as the carbon source of the carbon coating layer, and the graphitization ratio of the pre-sintered carbon is higher, so that a better conductive network can be constructed, and the conductivity of the carbon coating layer is improved; at the same time, the pre-sintered carbon reduces the number of functional groups on the surface during the sintering process, thereby reducing the catalytic decomposition of the electrolyte by the carbon coating layer and reducing the occurrence of side reactions; and the use of pre-sintered carbon as the carbon source of the carbon coating layer can also increase the particle size of the phosphate material, and obtain a carbon-coated lithium-containing phosphate positive electrode material with a relatively small specific surface area, further reducing the occurrence of side reactions; therefore, under the synergistic effect of the carbon coating layer with a high graphitization ratio and a low surface functional group ratio and the large-sized particles, the carbon-coated phosphate material has better conductivity, fewer surface functional groups and a smaller specific surface area, which is beneficial to the capacity of the lithium-ion battery and can improve the electrochemical performance and cycle performance of the lithium-ion battery.
[0040] In the present invention, the carbon-coated particles of lithium phosphate positive electrode material refer to primary particles that have not been agglomerated.
[0041] In a preferred embodiment, the proportion of functional groups on the surface of the carbon-coated lithium phosphate positive electrode material is less than 1%. By controlling the proportion of functional groups on the surface of the carbon-coated lithium phosphate positive electrode material, it is beneficial to improve the cycle performance and electrochemical performance of the lithium-ion battery.
[0042] In a preferred embodiment, the particle size of the carbon-coated lithium phosphate positive electrode material is 0.3-12 μm, and the SPAN value is 9-10. By further optimizing the particle size and SPAN value of the carbon-coated lithium phosphate positive electrode material, particles of different particle sizes can be better matched, thereby improving the electrochemical performance of the carbon-coated lithium phosphate positive electrode material.
[0043] The present invention does not specifically limit the powder impedance of the carbon-coated lithium-phosphate positive electrode material. In some specific embodiments, the powder impedance of the carbon-coated lithium-phosphate positive electrode material is less than 1000Ω. By controlling the powder impedance of the carbon-coated lithium-phosphate positive electrode material, it can be ensured that it has high conductivity.
[0044] The present invention does not specifically limit the thickness of the carbon coating layer. In some specific embodiments, the thickness of the carbon coating layer is 0.5-20 nm. When the thickness of the carbon coating layer is within the range of 0.5-20 nm, the carbon-coated lithium phosphate positive electrode material can have both good coating and conductivity.
[0045] The present invention does not specifically limit the specific type of lithium-containing phosphate. In some specific embodiments, the lithium-containing phosphate includes at least one of lithium manganese phosphate, lithium iron phosphate and lithium manganese iron phosphate. The above lithium-containing phosphates all have low lithium ion conductivity and need to be carbon-coated.
[0046] In some preferred embodiments, when the lithium-containing phosphate is lithium manganese iron phosphate, the median particle size D of the particles is 50 1-1.2 μm; or, when the lithium-containing phosphate is lithium iron phosphate, the median particle size D 50 When the median particle size of lithium manganese iron phosphate and lithium iron phosphate is within the above range, carbon-coated lithium manganese iron phosphate and carbon-coated lithium iron phosphate have lower specific surface area, lower powder impedance, higher capacity retention rate and lower DC resistance change rate.
[0047] In a second aspect, the present invention also provides a method for preparing the above-mentioned carbon-coated lithium phosphate positive electrode material, comprising the following steps: S1. The organic carbon material and / or the inorganic carbon material is subjected to sintering treatment to obtain pre-sintered carbon; the sintering treatment temperature is 800-1200°C and the time is 3 hours; S2, raw materials including an iron source, a phosphorus source and a lithium source are chemically reacted and then sintered to obtain a lithium-containing phosphate; S3. The lithium-containing phosphate in step S2 and the pre-sintered carbon in step S1 are mixed, sintered and crushed to obtain a carbon-coated lithium-containing phosphate positive electrode material.
[0048] The present invention provides a method for preparing a carbon-coated lithium phosphate positive electrode material. By controlling the pre-sintering process conditions of the pre-sintered carbon material to sinter at a temperature of 800-1200°C for more than 3 hours, a pre-sintered carbon with a higher graphite ratio and a smaller number of surface functional groups can be obtained. By using the pre-sintered carbon as a carbon source and a sintered lithium iron manganese phosphate raw material, a carbon-coated lithium phosphate positive electrode material with large-sized particles and fewer surface functional groups is prepared, thereby improving the conductivity, cycle stability and electrochemical performance of the carbon-coated lithium phosphate positive electrode material.
[0049] In a preferred embodiment, the inorganic carbon material includes at least one of graphite, carbon nanotubes, graphene, acetylene black, carbon fiber, carbon black, hard carbon, soft carbon and graphyne. The pre-sintered carbon prepared by using the above inorganic carbon material is conducive to obtaining pre-sintered carbon with a higher graphitization ratio.
[0050] In a preferred embodiment, the organic carbon material includes at least one of glucose, fructose, sucrose, maltose, starch, cellulose, citric acid, polyols, ascorbic acid, polyaniline, polyvinylidene fluoride, polytetrafluoroethylene, acrylonitrile and cyanamide and their derivatives. The use of the above organic carbon materials to prepare pre-sintered carbon is conducive to obtaining a better connected conductive network.
[0051] In a preferred embodiment, the sintering temperature of the sintering treatment in step S1 is 1000-1200° C. When the sintering temperature is within the above range, pre-sintered carbon with a higher graphitization ratio and a lower proportion of functional groups on the surface can be obtained.
[0052] The present invention does not particularly limit the chemical method used in preparing the lithium-containing phosphate, as long as it is suitable for preparing the lithium-containing phosphate. In some specific embodiments, the chemical reaction in step S2 adopts at least one of a sol-gel method, a solid phase reaction method, a hydrothermal method, a spray drying method, and a coprecipitation method. By adopting the above methods, lithium-containing phosphate can be prepared.
[0053] The present invention does not particularly limit the iron source used in preparing the lithium-containing phosphate, as long as it is suitable for preparing the lithium-containing phosphate. In some specific embodiments, the iron source in step S2 includes at least one of iron-containing phosphate, hydrogen phosphate, dihydrogen phosphate, carbonate, formates, acetates, oxides, citrates, oxalates and chlorides. The lithium-containing phosphate can be prepared using the above iron sources.
[0054] The present invention does not particularly limit the lithium source used in preparing the lithium-containing phosphate, as long as it is suitable for preparing the lithium-containing phosphate. In some specific embodiments, the lithium source in step S2 includes at least one of lithium-containing phosphate, hydrogen phosphate, dihydrogen phosphate, carbonate, formates, acetates, oxides, citrates, oxalates and chlorides. The lithium-containing phosphate can be prepared using the above lithium sources.
[0055] The present invention does not particularly limit the manganese source used in preparing the lithium-containing phosphate, as long as it is suitable for preparing the lithium-containing phosphate. In some specific embodiments, the manganese source includes at least one of manganese-containing phosphate, hydrogen phosphate, dihydrogen phosphate, carbonate, formates, acetates, oxides, citrates, oxalates and chlorides. The lithium-containing phosphate can be prepared using the above manganese sources.
[0056] The present invention does not specifically limit the phosphorus source used in preparing the lithium-containing phosphate, as long as it is suitable for preparing the lithium-containing phosphate. In some specific embodiments, the phosphorus source in step S2 includes at least one of phosphate, dihydrogen phosphate and phosphoric acid. The lithium-containing phosphate can be prepared using the above phosphorus sources.
[0057] The sintering process in step S2 and step S3 of the present invention is suitable for preparing lithium-containing phosphate and carbon-coated lithium-containing phosphate positive electrode materials. In some specific embodiments, the sintering temperature in step S2 and step S3 is 500-800 ° C and the time is 4-12 h. The lithium-containing phosphate and carbon-coated lithium-containing phosphate can be prepared by the above sintering process.
[0058] By using different molar ratios of manganese source, iron source, phosphorus source and lithium source, lithium-containing phosphates with different manganese and iron contents can be obtained. The present invention does not specifically limit the usage ratio of manganese source, iron source, phosphorus source and lithium source in step S2, and lithium-containing phosphates can be prepared. In some specific embodiments, the molar ratio of manganese source, iron source, phosphorus source and lithium source in the raw material of step S2 is (1-x): x: 1: 1.01, wherein 0 ≤ x ≤ 1. When the molar ratio of manganese source, iron source, phosphorus source and lithium source is within the above range, lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate can be prepared.
[0059] The thickness of the carbon coating layer can be adjusted by adjusting the ratio of the amount of the lithium-containing phosphate and the pre-sintered carbon. The ratio of the amount of the lithium-containing phosphate and the pre-sintered carbon in the present invention can be conventional in the art. In some specific embodiments, the mass ratio of the lithium-containing phosphate to the pre-sintered carbon in step S3 is 1:(0.005-0.03). When the mass ratio of the lithium-containing phosphate to the pre-sintered carbon is within the above range, it is beneficial to obtain a carbon-coated lithium-containing phosphate with good coating and conductivity.
[0060] In a third aspect, the present invention further provides a positive electrode sheet, which is prepared from the carbon-coated lithium-containing phosphate positive electrode material. The positive electrode sheet prepared using the carbon-coated lithium-containing phosphate has good cycle performance and electrochemical performance.
[0061] In a fourth aspect, the present invention further provides a lithium-ion battery, which uses the positive electrode sheet. The lithium-ion battery using the positive electrode sheet also has good cycle performance and electrochemical performance.
[0062] The technical scheme of the present invention is further illustrated below in conjunction with specific examples. All parts, percentages, and ratios described in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0063] Example 1
[0064] This embodiment provides a carbon-coated lithium manganese iron phosphate material, which is prepared by the following steps: (1) In an argon protective atmosphere, glucose was sintered at 900 °C for 8 h to obtain pre-sintered carbon; (2) Under a nitrogen atmosphere, manganese nitrate, iron nitrate, lithium nitrate and ammonium dihydrogen phosphate are weighed respectively according to the atomic ratio of manganese: iron: lithium: phosphorus of 0.6:0.4:1.01:1, and then manganese nitrate, iron nitrate, lithium nitrate and ammonium dihydrogen phosphate are added into water to form a transparent solution; the transparent solution is placed in a reaction kettle, stirred at 200 °C and 150 rpm / min for 5 h, and after obtaining a hydrothermal product, it is filtered and dried to obtain a lithium iron manganese phosphate precursor; under a nitrogen atmosphere, the lithium manganese phosphate precursor is placed in a box furnace, the heating rate is set to 2 °C / min, the temperature is raised to 550 °C, and then sintered for 8 h to obtain a lithium iron manganese phosphate raw material; (3) The lithium manganese iron phosphate raw material obtained in step (2) and the pre-sintered carbon obtained in step (1) are mixed in a mass ratio of 1:0.03 to obtain a mixture; the mixture is placed in a sand mill for sand grinding, and after sand grinding for 3 hours, it is spray dried, and then sintered at 720°C for 8 hours in a box furnace under nitrogen protection, and then crushed to obtain a carbon-coated lithium manganese iron phosphate material, which is marked as sample A1.
[0065] Example 2
[0066] This embodiment provides a carbon-coated lithium manganese iron phosphate material, which is different from Example 1 in that the raw material for preparing pre-sintered carbon is citric acid, the sintering temperature is 1000°C, the sintering time is 3 h, and the obtained carbon-coated lithium manganese iron phosphate material is marked as sample A2.
[0067] Example 3
[0068] This embodiment provides a carbon-coated lithium manganese iron phosphate material, which is different from Embodiment 1 in that the sintering temperature in step (3) is 700° C. and the sintering time is 8 h. The obtained carbon-coated lithium manganese iron phosphate material is marked as sample A3.
[0069] Example 4
[0070] This embodiment provides a carbon-coated lithium iron phosphate material, which is different from Example 1 in that the sintering temperature in step (1) is 850°C, the sintering time is 5 h, and no Mn source is added in step (2). The obtained carbon-coated lithium iron phosphate material is marked as sample A4.
[0071] Example 5
[0072] This embodiment provides a carbon-coated lithium iron phosphate material, which is different from Example 1 in that the sintering temperature in step (1) is 950°C, the sintering time is 6 h, and no Mn source is added in step (2). The obtained carbon-coated lithium iron phosphate material is marked as sample A5.
[0073] Comparative Example 1 This comparative example provides a carbon-coated lithium manganese iron phosphate material, which is different from Example 1 in that step (1) is omitted and the pre-sintered carbon in step (3) is replaced by glucose.
[0074] Comparative Example 2 This comparative example provides a carbon-coated lithium iron phosphate material, which is different from Example 1 in that step (1) is omitted, no Mn source is added in step (2), and the pre-sintered carbon in step (3) is replaced by glucose.
[0075] The samples in the embodiments and comparative examples were subjected to performance tests, and the test methods and test results are as follows: Particle size test method: D in the present invention 10 It refers to the particle size value corresponding to the cumulative distribution percentage of particles reaching 10%, D 50 It refers to the particle size value corresponding to when the cumulative distribution percentage of particles reaches 50%, D 90 It refers to the particle size value corresponding to the cumulative distribution percentage of particles reaching 90%. D in the present invention 10 , D 50 , D 90 , D max , D min It can be obtained by testing with MS2000 laser particle size analyzer. The calculation formula of SPAN value is (D 90 -D 10 ) / D 50 ; Specific surface area test method: BET can be obtained by testing with a specific surface area tester.
[0076] Powder impedance test method: The conductivity in the present invention can be obtained by testing with a MCP-PD51 powder impedance tester.
[0077] I g / I d Test method: Place the powder to be tested in a Raman spectrometer for scanning test, where the Raman spectrum excitation light wavelength = 532 nm, the spot diameter ≤ 2 μm, and the wave number accuracy ≤ 2 cm -1 The Raman wavenumber acquisition range is 1000 cm -1 -2200 cm -1 , of which 1000-1500 cm -1 The integrated peak area is defined as I d , 1500 cm -1 -2200 cm -1 The integrated peak area is defined as I g , I g / I d is the ratio of the peak areas of the two; Functional group ratio test method: Take the sintered sample and potassium bromide at a mass ratio of 100:1, grind and mix, and then perform a tablet test. The test range is 500 cm -1 -2000 cm -1 ; 1600 cm -1 -1800 cm -1 The absorption peak at 900 cm is the C=O stretching vibration absorption peak. -1 -1200 cm -1 The absorption peak at is the stretching vibration of PO. The strongest peak transmittance value in this range is taken to define IC=O and IP-O, respectively, and the functional group ratio is calculated as IC=O / IP-O.
[0078] Capacity retention rate and DCR growth rate: 1 kg of the carbon-coated lithium-containing phosphate material provided in the embodiment and the comparative example was mixed with a conductive agent and PVDF in a ratio of 95:2.5:2.5 to prepare a slurry, and then coated on an aluminum foil to form a pole piece with a surface density of 14 mg / cm 2 , assemble the pole piece and the graphite negative electrode into a battery, inject 3.5 g of liquid, and then perform hot pressing. The formation temperature is 70 ℃, the pressure is 120 KPa, and the formation voltage is 4.25 V. The selected formed batteries are cycled for 500 weeks at 1 C at 45 ℃.
[0079] The test results of the embodiments and comparative examples are shown in Table 1, Table 2 and Table 3. The samples in Examples 1-3 and the sample in Comparative Example 1 all use lithium iron manganese phosphate as the core, and the corresponding data values can be directly compared; while the samples in Examples 4-5 and Comparative Example 2 all use lithium iron phosphate as the core, and the corresponding data can be directly compared.
[0080] From the data in Table 1, it can be seen that the D 10 , D 50 , D 90 , D min and D max All of them are higher than the samples in Comparative Example 1; the D 10 and D 50 Higher than the sample in Comparative Example 2, while the D min and D max However, it is slightly lower than that of the sample in Comparative Example 2. The reason for this phenomenon may be that the particles of the sample in Comparative Example 2 agglomerated, affecting the measurement results.
[0081] It can be seen from the data in Table 2 that the samples in Examples 1-3 and the samples in Comparative Example 1 all use lithium iron manganese phosphate as the core. From the comparison of the BET values of the samples, it can be seen that the specific surface area of the samples in Examples 1-3 is smaller due to the use of pre-sintered carbon as the carbon source of the carbon coating layer. The samples in Examples 4-5 and Comparative Example 2 all use lithium iron phosphate as the core. From the comparison of the BET values of the samples, it can be seen that the specific surface area of the samples in Examples 4-5 is smaller. The powder impedance values of the samples in Examples 1-5 are all below 1000Ω, while the powder impedance values of the samples in Comparative Examples 1 and Comparative Example 2 are around 3000Ω. It can be seen that the samples in Examples 1-5 have lower resistance due to the use of pre-sintered carbon as the carbon source of the carbon coating layer; Samples I in Examples 1-5 g / I d The values are all above 1, while the I values of the samples in Comparative Examples 1 and 2 are g / I d All of them are below 1, indicating that Examples 1-5 use carbon with a higher graphitization ratio as the pre-sintered carbon as the carbon source, so that the graphitization ratio in the prepared carbon coating layer is higher; the functional group ratio of the samples in Examples 1-5 is as high as 0.35%, while the functional group ratios of the samples in Comparative Examples 1 and 2 are as high as 1.5% and 1.7%, indicating that Examples 1-5 use pre-sintered carbon with fewer surface functional groups as the carbon source, so that the sample surfaces have fewer functional groups.
[0082] It can be seen from the data in Table 3 that in Examples 1-3, due to the use of pre-sintered carbon as the carbon source of the carbon coating layer, the capacity retention rate and DCR growth rate of the samples are better than those of the sample in Comparative Example 1. Similarly, the capacity retention rate and DCR growth rate of the samples using pre-sintered carbon as the carbon source of the carbon coating layer in Examples 4-5 are better than those of the sample in Comparative Example 2. This shows that using pre-sintered carbon as the carbon source of the carbon coating layer can significantly improve the capacity retention rate of lithium-ion batteries and reduce the DCR growth rate, even if the lithium-ion battery has better cycle performance and electrochemical performance.
[0083]
[0084]
[0085]
[0086] Figure 1 is a data diagram of the capacity retention rate of the samples prepared in Example 1 and Comparative Example 1, Figure 2It is a schematic diagram of the change rate of direct current resistance (DCR) of the samples prepared in Example 1 and Comparative Example 1. It can be seen from the figure that sample A1 in Example 1 is significantly better than sample H1 in Comparative Example 1 in terms of capacity retention rate and direct current resistance change rate. In Example 1, glucose is converted into pre-sintered carbon with better conductivity at high temperature through pre-sintering, and sintered at 900°C, resulting in a lower content of tube energy groups. It is coated on the surface of lithium manganese iron phosphate as a conductive carbon source to enhance the conductivity of the material and reduce the residual surface functional groups, thereby reducing the side reactions of carbon-coated lithium phosphate positive electrode materials during the charge and discharge process; in addition, the growth restriction effect of pre-sintered carbon on lithium manganese iron phosphate is slightly weaker, which promotes the growth of lithium manganese iron phosphate, thereby reducing the contact area between the material and the electrolyte, reducing the impedance increase during the cycle, and further enhancing the cycle performance; in Comparative Example 1, glucose that has not been sintered is used as a carbon source to prepare There are many C=O functional groups on the surface of carbon-coated lithium manganese iron phosphate, which have nucleophilic effects and will catalyze the decomposition of the electrolyte during the charge and discharge process, causing a significant increase in the impedance of the cycle process; in addition, due to the low carbonization temperature, the degree of carbonization is weak, and the material conductivity is not strong, which can easily cause overcharging during the charge and discharge process, resulting in poor cycle performance; the glucose particles are relatively large, and have a stronger growth restriction effect on lithium manganese iron phosphate. The sintered particles are smaller and have a larger specific surface area, which increases the contact area with the electrolyte, and produces more side reactions during the cycle, affecting the cycle performance.
[0087] Figure 3 The infrared absorption spectra of the samples prepared in Example 1 and Comparative Example 1 are shown in FIG. As can be seen from the figure, the sample A1 in Example 1 has an infrared absorption spectrum of 900 cm -1 -1200 cm -1 The absorption peak of PO stretching vibration at 1600 cm -1 -1800 cm -1 The C=O stretching vibration absorption peak at is significantly weaker than that of sample H1, indicating that the surface of sample A1 has fewer functional groups.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbon-coated lithium-containing phosphate positive electrode material, characterized in that: The particles of the carbon-coated lithium phosphate positive electrode material have a composite structure, wherein the composite structure includes a lithium phosphate core and a carbon coating layer at least partially coated on the outside of the lithium phosphate core, wherein the carbon source of the carbon coating layer is pre-sintered carbon, and the carbon coating layer is g / I d ≥1.
2. The carbon-coated lithium-containing phosphate positive electrode material according to claim 1, characterized in that: The proportion of functional groups on the surface of the carbon-coated lithium phosphate positive electrode material is less than 1%; And / or, the particle size of the particles is 0.1-20 μm and the SPAN value is 9-10.
3. The carbon-coated lithium-containing phosphate positive electrode material according to claim 1, characterized in that: The powder impedance of the carbon-coated lithium-phosphate positive electrode material is less than 1000 Ω; And / or, the carbon coating layer has a thickness of 0.5-20 nm.
4. The carbon-coated lithium-containing phosphate positive electrode material according to claim 1, characterized in that: The lithium-containing phosphate includes at least one of lithium manganese phosphate, lithium iron phosphate and lithium manganese iron phosphate.
5. The carbon-coated lithium-containing phosphate positive electrode material according to claim 1, characterized in that: When the lithium-containing phosphate is lithium manganese iron phosphate, the median particle size D of the particles is 50 1-1.2μm; Or, when the lithium-containing phosphate is lithium iron phosphate, the median particle size D of the particles is 50 1.8-2μm.
6. A method for preparing the carbon-coated lithium-containing phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. The organic carbon material and / or the inorganic carbon material is subjected to sintering treatment to obtain pre-sintered carbon; the sintering treatment temperature is 800-1200°C and the time is more than 3 hours; S2, chemically reacting raw materials including a phosphorus source, a lithium source, an iron source and / or a manganese source and sintering the raw materials to obtain a lithium-containing phosphate; S3. The lithium-containing phosphate described in step S2 and the pre-sintered carbon described in step S1 are mixed, sintered and crushed to obtain a carbon-coated lithium-containing phosphate positive electrode material.
7. The method for preparing a carbon-coated lithium-containing phosphate positive electrode material according to claim 6, characterized in that: The inorganic carbon material in step S1 includes at least one of graphite, carbon nanotubes, graphene, acetylene black, carbon fiber, carbon black, hard carbon, soft carbon and graphyne; And / or, the organic carbon material in step S1 includes at least one of glucose, fructose, sucrose, maltose, starch, cellulose, citric acid, polyols, ascorbic acid, polyaniline, polyvinylidene fluoride, polytetrafluoroethylene, acrylonitrile and cyanamide and their derivatives.
8. The method for preparing a carbon-coated lithium-containing phosphate positive electrode material according to claim 6, characterized in that: The sintering temperature of the sintering treatment in step S1 is 1000-1200° C. and the time is 5-10 h.
9. The method for preparing a carbon-coated lithium-containing phosphate positive electrode material according to claim 6, characterized in that: The chemical reaction in step S2 adopts at least one of a sol-gel method, a solid phase reaction method, a hydrothermal method, a spray drying method and a co-precipitation method.
10. The method for preparing a carbon-coated lithium-containing phosphate positive electrode material according to claim 6, characterized in that: The iron source in step S2 comprises at least one of iron-containing phosphates, hydrogen phosphates, dihydrogen phosphates, carbonates, formates, acetates, oxides, citrates, oxalates and chlorides; And / or, the lithium source in step S2 includes at least one of lithium-containing phosphates, hydrogen phosphates, dihydrogen phosphates, carbonates, formates, acetates, oxides, citrates, oxalates and chlorides; And / or, the manganese source in step S2 includes at least one of manganese-containing phosphates, hydrogen phosphates, dihydrogen phosphates, carbonates, formates, acetates, oxides, citrates, oxalates and chlorides; And / or, the phosphorus source in step S2 includes at least one of phosphate, dihydrogen phosphate and phosphoric acid.
11. The method for preparing a carbon-coated lithium-containing phosphate positive electrode material according to claim 6, characterized in that: The sintering temperature in step S2 and step S3 is 500-800° C. and the sintering time is 4-12 h.
12. The method for preparing a carbon-coated lithium-containing phosphate positive electrode material according to claim 6, characterized in that: The molar ratio of the manganese source, the iron source, the phosphorus source and the lithium source in the raw material of step S2 is (1-x):x:1:(1-1.01), wherein 0≤x≤1; And / or, in step S3, the mass ratio of the phosphate to the pre-sintered carbon is 1:(0.005-0.03).
13. A positive electrode sheet, characterized in that: Prepared from the carbon-coated lithium phosphate positive electrode material according to any one of claims 1 to 4.
14. A lithium ion battery, characterized in that: The positive electrode sheet according to claim 12 is adopted.
Citation Information
Cited By
Phosphate material, modified phosphate material and preparation method thereof
CN120288736A
Positive electrode material and preparation method thereof, positive electrode plate, battery and electric equipment
CN120784325A
Preparation method of phosphate positive electrode material
CN121778689A
Method for producing a phosphate-based positive electrode material
CN121778689B